Вы находитесь на странице: 1из 2

Table of Laplace Transforms

- 1 f ( t ) = L { F ( - 1 s )}
- 1
f
(
t
)
= L
{
F
(
- 1
s
)}
F
(
s
)
= L
{
f
( )}
t
f
(
t
)
= L
{
F
(
s
)}
F
(
s
)
= L
{
f
( )}
t
1
1
at
1.
1
2.
e
s
s
- a
n
!
G
(
p
+ 1
)
n
3.
t
,
n =
1, 2, 3, K
4.
p
t
, p > -1
n + 1
s
p
+ 1
s
p
1 3
5
L
(
2
n
-
1
)
p
1
n -
5.
t
6.
t
2 , n =
1, 2, 3,
K
3
n +
1
n
2s
2
2
s
2
a
s
7.
sin (at)
8.
cos(at)
2
2
2
2
s
+ a
s
+ a
2as
2
s
2 - a
9.
t sin (at)
10.
t cos(at)
2
(
2
2
s
+ a
) 2
(
2
2
s
+
a
)
3
2
2a
2as
11.
sin (at)- at cos(at)
12.
sin (at)+ at
cos(at)
(
2
2
2
2
s
+ a
) 2
(
s
+ a
) 2
s
(
2
2
s
-
a
)
s
(
2
2
s
+
3a
)
13.
cos(at)- at sin (at)
14.
cos(at)+ at sin (at)
2
2
(
2
s
+ )
2
(
2
2
a
s
+
a
)
s sin
(
b
)
+ a cos
(
b
)
s cos
(
b
)
-
a sin
(
b
)
15.
sin (at + b)
16.
cos(at + b)
2
2
2
2
s
+ a
s
+
a
a
s
17.
sinh (at)
18.
cosh (at )
2
2
2
2
s
- a
s
- a
b
s
-
a
at
e
sin
(
bt
)
at
19.
20.
e
cos(
bt
)
2
2
(
s
- a
)
2
+ b
(
2
s
-
a
)
+
b
b
s
-
a
at
(
)
at
21.
e
sinh
bt
22.
e
cosh
(
bt
)
2
2
(
2
2
s
- a
)
- b
(
s
-
a
)
-
b
n
!
1
Ê
s
ˆ
n
at
23.
t e
,
n =
1, 2, 3,
K
24.
f
(ct)
F
n + 1
(
s
-
a
)
c
Á Ë
c
˜ ¯
- cs
u
(
t
)
= u
(
t - c
)
e
d (t - c)
25.
c
- cs
26.
e
Heaviside Function
s
Dirac Delta Function
-
cs F
- cs
27.
u
( )
t
f
(
t - c
)
e
(
s
)
28.
u
( )
t
g
( )
t
e
L
{
g
(
t
+
c
)}
c
c
ct
( )
n
n
(
n
)
29.
e
f
t
F (s - c)
30.
t
f
(
t
),
n = 1, 2, 3,
K
(
-
1
)
F
(
s
)
F
(s)
31.
1 f
( )
t
Ú
F
(
u
)
du
32.
Ú
f
(
v
)
dv
t
s
0 t
s
T
- st
Ú
e
f
( )
t
dt
33.
Ú
0 t f t -t g t dt
(
)
(
)
F (s)G(s)
34.
f
(t + T ) = f (t)
0
- sT
1 - e
2
35.
f
¢
(t)
sF (s)- f (0)
36.
f
¢¢
(t)
s
F
(
s
)
- sf
(
0
)
- f ¢
(
0
)
(
n
)
( )
n
n
-
1
n
-
2
(
(
(
)
n
-
2
)
(
)
(
)
(
)
n
-
1
)
37.
f
t
s
F
s
-
s
f
0
-
s
f
¢
0
L-
sf
0
-
f
(
0
)
© 2004 Paul Dawkins
1

Table Notes

1. This list is not inclusive and only contains some of the more commonly used Laplace transforms and formulas.

2. Recall the definition of hyperbolic trig functions. +

cosh ( ) =

t

e

t

e

-

t

2

sinh

( )

t

=

e

t

-

e

-

t

2

3. Be careful when using “normal” trig function vs. hyperbolic trig functions. The only difference in the formulas is the “+ a 2 ” for the “normal” trig functions becomes a “- a 2 ” for the hyperbolic trig functions!

4. Formula #4 uses the Gamma function which is defined as

G

( )

t

= Ú

0

e

- x

x

t

- 1

dx

If n is a positive integer then,

G(n +1) = n!

The Gamma function is an extension of the normal factorial function. Here are a couple of quick facts for the Gamma function

© 2004 Paul Dawkins

p

(

p

+

1

)(

G

(

p

p

+

2

)

G

+ 1 ) = p G ( p ) L ( p + n -
+
1
)
=
p
G
(
p
)
L
(
p
+
n
-
1
)
=
Ê
1 ˆ
=
p
Ë Á
2 ¯ ˜

2

G

(

p

+

n

)

G

(

p

)